2017
DOI: 10.15416/ijcp.2017.6.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Prevalence of Chronic Kidney Disease in Type‑2 Diabetes Mellitus Patients at Primary Healthcare Centers in Yogyakarta Province 2015

Abstract: AbstrakPengendalian glikemik yang baik pada diabetes melitus tipe 2 (DMT2) terbukti dapat mencegah penyakit komplikasi akibat DMT2. Puskesmas sebagai sarana pelayanan kesehatan primer merupakan garda terdepan yang diharapkan dapat memberikan pelayanan pengelolaan DMT2 dengan baik untuk mencegah penyakit komplikasi seperti penyakit gagal ginjal kronik (GGK). Kejadian GGK yang seringkali tanpa gejala spesifik serta keterbatasan pemeriksaan diagnostik di puskesmas menyebabkan keterlambatan diagnosis GGK maupun pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Finally, we demonstrate a high prevalence of DM in the age group above 40 years, and female gender higher than male gender, similarly to the studies reported previously (24), and contrary to those reported in India where there were more males than females (25). The duration of suffering from DM in this patient varied between 1 to 20 years, being most of the patients suffering from DM for less than 5 years.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we demonstrate a high prevalence of DM in the age group above 40 years, and female gender higher than male gender, similarly to the studies reported previously (24), and contrary to those reported in India where there were more males than females (25). The duration of suffering from DM in this patient varied between 1 to 20 years, being most of the patients suffering from DM for less than 5 years.…”
Section: Discussionsupporting
confidence: 89%
“…The results of previous studies showed that there was a significant relationship between glycemic control using the Glycated-Albumin parameter and the incidence of CKD (p 0.003; OR 1.75 CI 95% 0.92-3.32), which means the possibility of patients with poor glycemic control. Compared to patients with good glycemic control for chronic kidney disease is 1.75 or it can also be stated that poor glycemic control can increase the likelihood of chronic kidney disease incidence by 63.64% 13 . Figure 3 shows the scatter plot results of chronic kidney disease prevalence and the percentage of habitual drinking soft drinks >1 time/day.…”
Section: Resultsmentioning
confidence: 99%
“…Ghoreishi et al (2019) showed that selfregulation was a determinant in the self-care of diabetic patients, and was statistically significant (p<0.001). Nazari et al (2019) showed self-regulation as a direct predictor of physical activity in female patients with type 2 diabetes. Castonguay et al (2018) showed the importance of self-regulation of adherence to behaving in physical activity in patients with type 2 diabetes.…”
Section: Effect Of Self-regulation On Type 2 Diabetes Tertiary Prevention Behaviormentioning
confidence: 97%